Management of Buffer Stocks of Energy Based on Local Resources in Disaster-Prone Areas - Husnah, Husnah; Wahyuningsih, Wahyuningsih; Asngadi, Asngadi (Opción, 2019)
In the aftermath of a disaster, it is the unavailability of energy which causes the worst further economic, social and environmental distress. Optimal man- agement before the disaster, at the preparedness stage, is a top priority and the best solution. We analyse the role of buffer stock management in disas- ter-prone areas, and develop a management model for the local resource of energy in this instance, coconut shell charcoal briquettes to establish power security beforehand and to remain environmentally friendly. The theoretical implications of this study enrich the literature in strategic planning and pro- duction, and the practical results are that communities stockpile energy based on local resources. Our findings apply throughout the world. All disaster are- as, rural or urban, require a buffer stock of energy.